GE_GERICHTE P/3803/2018 vom 10. Februar 2022 - GE Cour de justice (2022)
INCENDIE INTENTIONNEL;VOL(DROIT PÉNAL);DOMMAGES À LA PROPRIÉTÉ(DROIT PÉNAL);VIOLATION DE DOMICILE | CP.221; CP.186; CP.144.al1; CP.139.ch1